Dual Diagnosis: Rheumatoid Arthritis and Multiple Sclerosis. Issue 1 (15th January 2014) - Ozsahin, Mustafa; Dikici, Suber; Kocaman, Gülsen; Besir, Fahri Halit; Baltaci, Davut; Ataoglu, Safinaz
Abstract : Juvenile rheumatoid arthritis (JRA) is the most common rheumatologic disease in children. Moreover, multiple sclerosis (MS) is the most frequent demyelinating disease and has been associated with various chronic inflammatory diseases. However, its association with JRA has not been frequently described. Autoimmunity in both JRA and MS has been documented in the scientific literature, although there has been no definitive finding that patients with JRA are prone to the development of MS. An increasing frequency of MS resulting from an increased use of antitumor necrosis factor agents in the treatment of rheumatoid arthritis and other chronic inflammatory diseases has been reported recently. In this study, we report on the development of MS in a patient with JRA who did not have a history of antitumor necrosis factor use.